Deeper Magic: Re-engaging the Virtues in School and Parish1. Issue 2 (30th June 2015) - Milbank, Alison
Abstract This essay argues that modern society lacks a vision of the common good, which prevents education from having an adequate telos or goal. It calls for a restoration of the language of virtue and the ethical tradition of Aristotle and Aquinas. The Anglican parish and the church primary or elementary school are examined as sites where virtue ethics is still active: particularly in the intercessory work of parish prayer, and in the mimetic approach to learning employed with younger children. The article then addresses ways in which these institutions depend upon what C.S. Lewis called 'deeper magic' of a transcendent reality, and ways in which the school especially might develop further a pedagogy of the virtues using J.K. Rowling's Harry Potter stories as exemplars. Finally, it argues for a dimension of the beautiful in a recovery of an education in Christian virtue.